Mitochondrial gene expression, antioxidant responses, and histopathology after cadmium exposure. Issue 8 (15th October 2012) - Al Kaddissi, Simone; Legeay, Alexia; Elia, Antonia Concetta; Gonzalez, Patrice; Floriani, Magali; Cavalie, Isabelle; Massabuau, Jean‐Charles; Gilbin, Rodolphe; Simon, Olivier
<x xml:space="preserve">Abstract</x> The present study investigates cadmium effects on the transcription of mitochondrial genes of Procambarus clarkii after acute (0.05, 0.5, and 5 mg Cd/L; 4–10 days) and chronic exposures (10 μg Cd/L; 30–60 days). Transcriptional responses of cox1, atp6, and 12S using quantitative real‐time RT‐PCR were assessed in gills and hepatopancreas. Additionally, the expression levels of genes involved in detoxification and/or oxidative stress responses [mt, sod(Mn)] and enzymatic activities of antioxidants (SOD, CAT, GPX, and GST) were analyzed. The histopathological effects in hepatopancreas of crayfish were evaluated by light microscopy. Relationships between endpoints at different levels of biological organization and Cd bioaccumulation were also examined. Cd induced high levels of bioaccumulation, which was followed by mitochondrial dysfunction and histological alterations in both experiments. Moreover, perturbations in the defence mechanisms against oxidative stress tended to increase with time. Results also showed that molecular responses can vary depending on the intensity and duration of the chemical stress applied to the organisms and that the study of mt gene expression levels seemed to be the best tool to assess Cd intoxication. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 893–907, 2014.